Analisis Bpjs Ketenagakerjaan Dalam Upaya Meningkatkan Kesejahteraan Tenaga Kerja Khususnya Petani Di Bangun Purba - Nur Aprillia; Fauzi Arif Lubis (STIE AMKOP, 2023)
Workers in Indonesia currently really need social security for themselves, with this social security they can focus more on carrying out their duties until they are finished. With social security, the welfare of workers itself has a good impact on family survival in the future. If one day a work accident occurs while they are carrying out their duties, family members can enjoy financial assistance from the government through this social security. This study uses a qualitative method, namely a research procedure that produces descriptive data in the form of written or spoken words from people or observable behavior. This method also comes from actions that are used as an understanding based on phenomena that occur in society, especially farmers. In influencing workers, BPJS Ketenagakerjaan has functions for workers, namely: Organizing work accident insurance programs, Organizing death security programs, Organizing old age security programs, Organizing pension insurance programs. The conclusion in this study is that there are still many farmers who do not take part in the BPJS Employment Program. As well as the lack of awareness from farmers about the benefits of Employment BPJS for them in the event of a work accident. Keywords: Employment BPJS, Welfare, Labor, Farmers